Status of Haematocrit Level in COPD Patient Admitted in Rajshahi Medical College Hospital - Md Rezaul Islam; Muhammad Shakhawath Hossain; Ahmed Imran Kabir; Md Mozammel Hoque; Goutam Sen; Mohammed Mirazur Rahman; Md Masudur Rahman; Md Hosna Sadat Patwary; Md Jakaria Mahmud; Md Ziaul Karim; Mir Iftekhar Mostafiz; Rezaul Haque; et al. (Chest & Heart Journal, 2026)
Introduction: COPD is a common, preventable and treatable disease which is characterized by persistent respiratory symptoms and airflow limitation that is due to airway and/or alveolar abnormalities usually caused by significant exposure to noxious particles or gases.1–3 It is a leading cause of chronic morbidity and mortality worldwide that includes an economic and social burden which is both substantial and increasing.1,4 Aim of the study: The aim of the study was to observe the haematocrit status in COPD patients admitted in Rajshahi Medical College Hospital. Methods: This cross-sectional study was performed in the Department of Medicine, Rajshahi Medical College Hospital, Bangladesh, from March 2022 to February 2023. After careful history taking, examination and appropriate investigations fulfilling inclusion and exclusion criteria, total 100 clinically diagnosed COPD patients with a FEV1/vital capacity (FVC) ratio